The economics of carpeting and resilient flooring : an evaluation and comparison - Parks, George M (Industrial Research Unit study ;, 1966)
This study examines the carpeting-resilient flooring controversy, an excellent case for classroom use, particularly in courses on business policy and industrial engineering.